Concurrent training and taurine improve lipid profile in postmenopausal women - Buonani, Camila [UNESP]; Rossi, Fabrício Eduardo; Diniz, Tiego Aparecido; Fortaleza, Ana Claúdia; Viezel, Juliana [UNESP]; Picolo, Malena Ricci [UNESP]; Fernandes, Rômulo A. [UNESP]; Júnior, Ismael Forte Freitas [UNESP] (FapUNIFESP (SciELO), 2019)
Introduction: Taurine plays an important role in metabolism and can positively influence body composition, since it is believed that in appropriate concentrations this amino acid (AA) can reduce perceived exertion, thereby delaying the onset of fatigue; however, the effect of this AA combined with concurrent training in postmenopausal women is unknown. Objective: To analyze the effects of concurrent training (aerobic+resistance) and taurine supplementation on the metabolic profile of postmenopausal women. Methods: Forty-three postmenopausal women were randomly divided into the following groups: Control (C [N=13]), Taurine (T [N = 8]), Taurine+Exercise (TE [N=13]), and Placebo+Exercise (E [N=9]). The supplemented groups received capsules corresponding to a daily taurine intake of 1.5 g. Concurrent training (CT) took place three times a week and consisted of 50 minutes of resistance training and 30 minutes of aerobic training. Body composition was assessed using DXA, in addition to biochemical profile analysis: triglycerides, total cholesterol, low-density lipoprotein cholesterol and high-density lipoprotein cholesterol. The intervention period lasted for eight weeks. Statistical significance was set at 5%. Results: The TE group presented a statistical reduction in terms of relative change in the percentage of total body fat (%) (-4.1±3.0) and trunk fat (%) (-4.4±3.9), with greater lean body mass (kg) gain (3.9±2.5) when compared to groups C(0.3±3.7, p=0.005; 0.8±4.3, p=0.024; -1.1±3.1, p<0.001; respectively) and T (1.2±3.4, p=0.004; 1.6±5.4, p=0.023 -1.2±2.9; p=0.002; respectively). The TE group presented a greater percentage reduction of total cholesterol (-5.8±7.1 mg/dl) when compared to group T (11.5±19.1 mg/dl). The TE group presented a significant decrease in LDL-c (-13.6±9.2 mg/dl) compared to groups C (3.5±13.9 mg/dl, p=0.014) and T (9.9±24.3 mg/dl, p=0.027). Conclusion: The combination of concurrent training and taurine supplementation promoted a reduction in total cholesterol and LDL-c levels in postmenopausal women. Level of Evidence I; Study type: Randomized clinical study.
Entrenamiento concurrido junto con taurina mejora perfil lipídico en mujeres posmenopáusicas
Treinamento concorrente e taurina melhoram perfil lipídico em mulheres pós menopausa
Keywords: Body composition; Metabolism; Resistance training